Antimicrobial properties of yuzu and lime oils and their storage stabilities in inclusion complex with cyclodextrin and oil-in-water emulsion - Watanabe, Yoshiyuki; Hinohara, Tomoyuki; Nishioka, Nobuhiro; Uda, Yasutaka; Suzuki, Katsuyuki; Nomura, Masato (Science, Engineering and Health Studies, 2018)
We examined the antimicrobial properties of two essential oils obtained from yuzu (Citrus junos) and lime (C. aurantifolia) against ten microorganisms. We also kinetically examined the storage stability of the inclusion complex with β-cyclodextrin and oil-in-water emulsion prepared using the oils by measuring remaining limonene in each system. Both yuzu and lime oils effectively inhibited the growth of bacilli; however, there was the difference in their antimicrobial activities against fungi. We estimated the rate constant k for the disappearance of limonene in each oil and found that in comparison with bulk system, the inclusion complex had high stability, whereas the emulsion had low stability. Limonene in yuzu oil had lower k values than that in lime oil in the inclusion complex but not in the emulsion. We suggest that more compounds with polar groups (such as terpene alcohol) in lime oil can lead to differences in antimicrobial properties between the two oils and influence the stability of the inclusion complex and emulsion.